Experimental Design: Javanese Folktale Preservation Using Augmented Reality Technology - Permatasakti, Damba; Basiroen, Vera Jenny (Humaniora, 2018)
This research was conducted to discover innovative and interesting methods to preserve also to reintroduce Javanese folktale to today?s society. The data were gathered from primary research through quantitative research to 104 respondents to know about folktale and opinion of modern preservation medium such as augmented reality medium, and also qualitative research through an in-depth interview to enrich the researcher?s fashion knowledge about printed technic and fabrics. Besides primary research, the researchers also conducted secondary research through various sources such as websites, e-articles, survey, and interview. The result of this research is an interactive scarf as a collaboration of fashion accessory as a physical medium and augmented reality technology to enhance its interactive experience. Based on the survey held, the most favorite fashion accessory among woman from the age of 18 until 30 years old is a scarf. Most women will have a scarf inside their bag, just in case they need it. By making an illustration of Javanese folktale on a scarf, it will hopefully attract the target market to retrace their memory and raise people?s awareness about Javanese folktale that seems to be forgotten in today?s era. The usage of augmented reality feature in this research is to give further information such as videos, images, or texts towards the illustration of the scarf by scanning the pattern by using the user?s smartphone.